2019
DOI: 10.1016/j.semnephrol.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Mineral Metabolism in AKI

Abstract: Dysregulated mineral metabolism is a nearly universal sequalae of acute kidney injury (AKI). Abnormalities in circulating mineral metabolites observed in patients with AKI include hypocalcemia, hyperparathyroidism, hyperphosphatemia, decreased vitamin D metabolite levels, and increased fibroblast growth factor 23 levels. We review the pathophysiology of dysregulated mineral metabolism in AKI with a focus on calcium, phosphate, parathyroid hormone, and vitamin D metabolites. We discuss how mineral metabolite le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 178 publications
(195 reference statements)
1
49
0
1
Order By: Relevance
“…Hyperphosphatemia is a common complication of RM with several proposed pathogenic factors, including the release of inorganic phosphorus into the plasma and reduced urinary phosphate excretion [26,27]. In the present study, increased serum phosphate was determined to be an independent predictor for AKI-associated RM, which is in accordance with previously reported findings [28,29].…”
Section: Discussionsupporting
confidence: 92%
“…Hyperphosphatemia is a common complication of RM with several proposed pathogenic factors, including the release of inorganic phosphorus into the plasma and reduced urinary phosphate excretion [26,27]. In the present study, increased serum phosphate was determined to be an independent predictor for AKI-associated RM, which is in accordance with previously reported findings [28,29].…”
Section: Discussionsupporting
confidence: 92%
“…Hyperphosphatemia is a common complication of RM with several proposed pathogenic factors, including the release of inorganic phosphorus into the plasma and reduced urinary phosphate excretion [ 32 , 33 ]. In the present study, increased serum phosphate was determined to be an independent predictor for AKI-associated RM, which is in accordance with previously reported findings [ 11 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous AKI investigations, underlying comorbidities (diabetes mellitus, severe liver diseases, chronic kidney disease) [ 28 , 29 ] and recent use of RAS inhibitors or potassium-sparing diuretics [ 19 ] were identified in the present CA-AKI hospitalization risk score. The risk model also indicated that low calcium levels and high phosphorus levels were potentially modifiable predictors and could be targeted for correction [ 30 ]. This feature has substantial clinical implications because it demonstrates that the model can be applied to prospectively support clinical decision systems in real time for rapid screening and recognition of patients with a predicted risk of CA-AKI in outpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients with CA-AKI in the final cohort were older (65.26, SD 15.49 years) than those in the non-CA-AKI group; moreover, 54.4% of the patients were women and 50.67% had preexisting chronic kidney disease (eGFR<60 ml/min/1.73m 2 at baseline). In comparison, a study with a British population reported a mean age of 74.4 (SD 15.4) years, 50%-52% female patients, and 31.9%-34.6% of patients with preexisting chronic kidney disease [ 4 , 30 ], whereas another study with a US population reported a mean age of 67.8 (SD 12.2) years and 43.2% of patients with preexisting chronic kidney disease [ 3 ]; these populations were considered to be comparable with the CA-AKI patients identified using KDIGO SCr-based criteria in different populations. The present study used large-scale clinical data with a representative and adequate sample size to develop a diagnostic tool for CA-AKI risk evaluation.…”
Section: Discussionmentioning
confidence: 99%